Comparative anatomy of three Globularia (Plantaginaceae) taxa from Türkiye: New evidence for winged stem protrusions and myrosin-like cells - Çi̇lden Emre (Phytotaxa, 2026)
A comparative anatomical study was conducted on three Globularia taxa (G. orientalis, G. trichosantha and G. cordifolia) from Türkiye, which was based on examination of their root, stem and leaf structures using light microscopy. All taxa share diagnostic generic characters, including perennial root anatomy, equifacial (isobilateral) leaves with amphistomatic and anomocytic stomata, and the presence of both covering and glandular trichomes. Despite these similarities, several anatomically informative characters were identified. Winged stem protrusions, recorded here for the first time in G. trichosantha and G. cordifolia but absent in G. orientalis, represent a useful diagnostic feature within the genus. In addition, a distinct type of enlarged parenchyma cell resembling myrosin cells (“myrosin-like cells”) was observed in the root and stem tissues of all taxa. These cells may represent specialised elements involved in the storage or metabolism of secondary compounds found in Globularia. Comparative evaluation of published cytological data indicates pronounced ploidy variation in G. cordifolia, supporting its treatment as the “G. cordifolia species complex” and highlighting its morphological and anatomical plasticity. Overall, the results provide new diagnostic characters relevant to species delimitation and establish a structural basis for future histochemical, ultrastructural and molecular research into evolutionary relationships within Globularia.